Astragalus-containing Chinese herbal medicine used with Western medicine for lupus nephritis: a systematic review and meta-analysis of randomized controlled trials - Li, Jinjiao; Wu, Mengyun; Liu, Weiwei (Frontiers in Pharmacology, 2025)
BackgroundLupus nephritis (LN) is a serious complication of systemic lupus erythematosus (SLE) that requires effective management to prevent kidney damage and other systemic effects. While Western medicine provides the standard treatment, incorporating traditional Chinese medicine, such as Astragalus-containing Chinese herbal medicine (CHM), may offer additional benefits in improving patient outcomes.ObjectiveThis study aims to conduct a systematic review and meta-analysis of the efficacy and safety of Astragalus in conjunction with Western medicine for the treatment of LN.MethodsWe conducted a comprehensive, global systematic search across databases including PubMed, Web of Science, Embase, China National Knowledge Infrastructure (CNKI), and Wanfang. Data were synthesized using fixed- or random-effects models, depending on the level of heterogeneity. Results were presented as standardized mean difference (SMD), risk ratios (RRs), or number needed to treat (NNT) with 95% confidence intervals (CIs). The Cochrane Q test and I2 statistics were used to test the heterogeneity assessment. Trial sequential analysis (TSA) was employed to assess the power of the results. All statistical analysis was carried out using STATA (version 16.0).ResultThe analysis included 14 RCTs, with a total of 800 patients (417 in the treatment group and 383 in the control group). Our meta-analysis revealed that patients treated with Astragalus-containing CHM alongside Western medicine showed markedly improved outcomes compared to those receiving only Western medicine. Significant improvements were observed in Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) scores (SMD = 1.01, 95% CI: 0.71–1.30, P < 0.001), 24-h proteinuria (SMD = 0.51, 95% CI: 0.35–0.66, P < 0.001SMD = 0.51, 95% CI: 0.35–0.66, P < 0.001), serum creatinine (SCr) levels (SMD = 0.64, 95%CI: 0.27–1.01, P < 0.001), blood urea nitrogen (BUN) levels (SMD = 0.73, 95%CI: 0.53–0.92, P < 0.001), and overall response rates (ORR) (RR = 1.21, 95%CI: 1.10–1.34, P < 0.001). Additionally, the incidence of adverse events (AEs), such as diarrhea, fever, and other symptoms, was significantly lower in the group treated with Astragalus-containing CHM and Western medicine (RR = 0.56, 95%CI: 0.42–0.73, P < 0.001). The TSA indicated that the data were sufficiently robust to draw reliable numerical conclusions regarding the ORR and the incidence of AEs.ConclusionThe inclusion of Astragalus-containing CHM alongside Western medicine may be a promising strategy for to improve the therapeutic effectiveness and reduce toxicity in the treatment of LN.